2007
DOI: 10.1152/ajpheart.00229.2007
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance between endothelium-derived relaxing and contracting factors in mesenteric arteries from aged OLETF rats, a model of Type 2 diabetes

Abstract: We investigated whether the balance between endothelium-derived relaxing factors (EDRFs) and endothelium-derived contracting factors (EDCFs) might be altered in mesenteric arteries from aged Otsuka Long-Evans Tokushima Fatty (OLETF) rats (a Type 2 diabetic model) [vs. age-matched control Long-Evans Tokushima Otsuka (LETO) rats]. ACh-induced relaxation was impaired in the OLETF group, and a tendency for the relaxation to reverse at high ACh concentrations was observed in both groups. This tendency was abolished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
114
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(120 citation statements)
references
References 53 publications
(123 reference statements)
5
114
0
1
Order By: Relevance
“…2,10,11,37) Moreover, we found that endothelium-dependent vasorelaxation of isolated aortas in response to ACh was improved by MO in diabetic mice and showed a marked tendency to improve by CA and RV; because the polyphenols reduced TXA 2 levels in the aorta, the subsequent reduction of contraction factors may, at least in part, account for the observed improvement of endothelium-dependent vasorelaxation. That is, the polyphenols did not modify ACh-stimulated NO production, but suppressed TXA 2 levels in the diabetic aorta.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…2,10,11,37) Moreover, we found that endothelium-dependent vasorelaxation of isolated aortas in response to ACh was improved by MO in diabetic mice and showed a marked tendency to improve by CA and RV; because the polyphenols reduced TXA 2 levels in the aorta, the subsequent reduction of contraction factors may, at least in part, account for the observed improvement of endothelium-dependent vasorelaxation. That is, the polyphenols did not modify ACh-stimulated NO production, but suppressed TXA 2 levels in the diabetic aorta.…”
Section: Discussionmentioning
confidence: 68%
“…[8][9][10][11][12][13][14][15][16]27,28) Plasma samples were stored at −20°C until analysis. Briefly, plasma glucose, cholesterol, high-density lipoprotein (HDL) cholesterol, triglyceride, and serum non-esterified fatty acid (NEFA) levels were each determined with a commercially available enzyme kit (Wako Pure Chemical Industries, Ltd., Osaka, Japan).…”
Section: Ca Mo and Rv Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the EDHF component of acetylcholine-induced relaxation was impaired in epineurial arterioles [19] and small mesenteric arteries [20] from Zucker fatty rats, a model of type 2 diabetes. EDHF-mediated responses have also been shown to be reduced in mesenteric arteries from aged Otsuka Long-Evans Tokushima fatty rats, another model of type 2 diabetes [21].…”
Section: Introductionmentioning
confidence: 99%
“…EDCFmediated vasoconstriction might prevail with increasing age, as well as disturbed endothelial function, for example, in hypertension 1,2 or type 2 diabetes. 3 In addition to reduced generation of vasodilator prostaglandins (PGs), such as PGI 2 , enhanced production of vasoconstrictor prostanoids has been described. 4,5 Oxygen-derived free radicals and isoprostanes, generated by exaggerated oxidative stress, are further members of the EDCF family.…”
mentioning
confidence: 99%